Uma análise sobre a inserção da norma ISO 50001 no setor industrial do Estado do Espírito Santo - Ferreira, Eberte Alves (2018)
The purpose of this dissertation is to analyze the insertion of the international standard "ISO 50001 - Energy Management Systems - Requirements with guidance for use" - which in Brazil had as standard "ABNT NBR ISO 50001 - Energy Management Systems - Requirements with guidelines for use" and analyze the insertion of it in the industrial sector of the State of Espírito Santo. Initially, the paper focuses on highlighting the importance of ISO 50001 for the industry and its direct relationship with energy efficiency. Using the national and foreign literature, one can find the potentialities and guidelines of an energy management system according to the proposals of the standard itself. In addition to a historical survey and the structural particularities, the impact of the standard in the industrial area is punctuated, within a sustainable perspective. The next section presents the relationship between public policies and energy management, where the Brazilian experience is also portrayed showing the institutional arrangement of agencies and government programs dealing with energy efficiency actions. In due course, a brief comment is made on ISO 50001 in the international, national and regional industrial scenario and the opportunities and benefits expected for society and industry are discussed. In this way, ISO 50001 becomes an interesting instrument for the promotion of sustainability in production processes. The core of the dissertation consists of an interpretative analysis that details the insertion of said norm in the industrial segment of the State of Espírito Santo. For this purpose, a case study was proposed that analyzes the adherence of the norm. The analysis of the regional experience was measured through personal interviews and the application of a questionnaire to the managers. Finally, we present the considerations from the case study that allowed recognizing some data, for example, that 66.7% do not know the norm.